Preference assessment training via self‐instruction: A replication and extension. Issue 4 (16th August 2016) - Shapiro, Marnie; Kazemi, Ellie; Pogosjana, Meline; Rios, Denice; Mendoza, Melissa
Abstract : We examined the effects of a self‐instructional and feedback package on participants' implementation of a paired‐stimulus preference assessment. Specifically, in Experiment 1, we used a multiple baseline design across participants to replicate and extend the results of Graff and Karsten (2012) by evaluating the effectiveness of their self‐instructional manual. A majority of the participants (i.e., 5 of 7 undergraduate students and 4 of 5 in‐home behavior technicians) achieved mastery with the self‐instructional package. The remaining participants met the mastery criterion after brief modeling and feedback sessions. In Experiment 2, we identified the most effective component of the feedback condition from Experiment 1 when a self‐instructional package was not sufficient. Brief feedback sessions in which participants received a list of the targeted responses plus information regarding accuracy of emitted responses was sufficient for 5 of 6 participants to achieve mastery.